Arsitektur Strategi Bisnis Dokumentasi Pernikahan Pada Iphotobride Wedding - Rachman, Mohammad Irfan; Asnawi, Yudha Heryawan; Hannan, Sufrin (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aimed to formulate a wedding documentation business strategy that can be applied to Iphotobride companies. Respondents in this study consisted of 8 consumer respondents who were selected using purposive sampling, 5 internal companies and 3 company partners from 2019 to 2021. This type of research used descriptive qualitative methods with analysis of Business Development Strategies using IFE, EFE, IE matrix, SWOT and QSPM. The results showed that Iphotobride had an IFE score of 3,130 and an EFE score of 2,413. In the IE matrix mapping, Iphotobride is in the Grow and Build position. The strategies that can be carried out by Iphotobride are backward, forward, horizontal integration, market penetration, market development, and product development. The alternative strategies obtained are influencer endorsement (collaboration with influencers), increase management ability to collaborate with some wedding vendors, product differentiation and services with competitors, injection of capital loans by Investors/Banks. The suggested priority strategy is to improve management's ability to collaborate with some wedding vendors and differentiate service products with competitors. Strategic architecture that Iphotobride might implement or run to become a competency in the future is to make an all in wedding service package, or